Learning physics with your smartphone - Córdova Martínez, María del Carmen Evangelina; Lima Llanllaya, Sarita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The educational process underwent a drastic change due to the pandemic we suffered worldwide, we had to learn to use technological tools in teaching and learning. Therefore, following this trend, we proposed the use of the application “Physics M-Lab” in its first version for the teaching of kinematics. As we are in the field of social sciences, we used a quasi-experimental design thatallowed us to conclude that learning improved significantly.